VHL deficiency augments anthracycline sensitivity of clear cell renal cell carcinomas by down-regulating ALDH2 - Yao-Hui Gao (Nature Portfolio, 2017)
The VHL tumour suppressor gene is lost in approximately 70% of clear cell renal cell carcinoma (ccRCC). In this study, the authors demonstrate that VHL loss in these tumours augments anthracyclines chemotherapy by down-regulation of ALDH2.